ANATOMI PEPAGAN PULAI DAN BEBERAPA JENIS SEKERABAT - Y I Mandang (Jurnal Penelitian Hasil Hutan, 2004)
Bark anatomy of white pulai (Alstonia scholaris R.Br.).  black pulai (Alstonia angustiloba Miq.) and bintaro (Cerbera manghas L.)  were observed and described for identification purposes.  These plants  have been used as sources of traditional medicine in South East Asia.  Bark of these trees exudes white gum when it was cut; the inner parts are white.  The outer surfaces of A. scholaris and C. manghas are gray and usually lenticellate; the outer surface of A.  angustiloba contains no lenticel, and the colour is dark brown .  with narrow and shallow longitudinal fissures.  The main components of bark are phloem, parenchyma, ray, fibre, sclereid and periderm. Fibres are tangentially arranged near the cambium ofjuvenile stem of all species, then pushed outward by cambium activity as the age of the plant  increased.  Sclereids were few  and thin walled while the plants  were young and then increased in quantity and in cell wall thickness as the plants become mature.  The main anatomical differences between bark of these plants were in the morphology of the sclereids.  Sclereids of A. scholaris are short and  chubby, sclereid of A.   angustiloba are long and stout  while those of C. manghas are long and slender. A tentative identification key is presented.